Comparison of Intrapulmonary and Systemic Pharmacokinetics of Colistin Methanesulfonate (CMS) and Colistin after Aerosol Delivery and Intravenous Administration of CMS in Critically Ill Patients - Boisson, Matthieu (Antimicrob Agents Chemother, 2014)
Colistin is an old antibiotic that has recently gained a considerable renewal of interest for the treatment of pulmonary infections due to multidrug-resistant Gram-negative bacteria. Nebulization seems to be a promising form of administration, but colistin is administered as an inactive prodrug, colistin methanesulfonate (CMS); however, differences between the intrapulmonary concentrations of the active moiety as a function of the route of administration in critically ill patients have not been precisely documented. In this study, CMS and colistin concentrations were measured on two separate occasions within the plasma and epithelial lining fluid (ELF) of critically ill patients (n = 12) who had received 2 million international units (MIU) of CMS by aerosol delivery and then intravenous administration. The pharmacokinetic analysis was conducted using a population approach and completed by pharmacokinetic-pharmacodynamic (PK-PD) modeling and simulations. The ELF colistin concentrations varied considerably (9.53 to 1,137 mg/liter), but they were much higher than those in plasma (0.15 to 0.73 mg/liter) after aerosol delivery but not after intravenous administration of CMS. Following CMS aerosol delivery, typically, 9% of the CMS dose reached the ELF, and only 1.4% was presystemically converted into colistin. PK-PD analysis concluded that there was much higher antimicrobial efficacy after CMS aerosol delivery than after intravenous administration. These new data seem to support the use of aerosol delivery of CMS for the treatment of pulmonary infections in critical care patients.